PPARα Modulation-Based Therapy in Central Nervous System Diseases - Deokho Lee (MDPI AG, 2021)
The burden of neurodegenerative diseases in the central nervous system (CNS) is increasing globally. There are various risk factors for the development and progression of CNS diseases, such as inflammatory responses and metabolic derangements. Thus, curing CNS diseases requires the modulation of damaging signaling pathways through a multitude of mechanisms. Peroxisome proliferator-activated receptors (PPARs) are a family of nuclear hormone receptors (PPARα, PPARβ/δ, and PPARγ), and they work as master sensors and modulators of cellular metabolism. In this regard, PPARs have recently been suggested as promising therapeutic targets for suppressing the development of CNS diseases and their progressions. While the therapeutic role of PPARγ modulation in CNS diseases has been well reviewed, the role of PPARα modulation in these diseases has not been comprehensively summarized. The current review focuses on the therapeutic roles of PPARα modulation in CNS diseases, including those affecting the brain, spinal cord, and eye, with recent advances. Our review will enable more comprehensive therapeutic approaches to modulate PPARα for the prevention of and protection from various CNS diseases.